Cuidado de enfermería y eventos adversos en una unidad de cuidados intensivos - Guibovich Arroyo, Diana Gissela (2020)
This descriptive, correlational cross-sectional research work was carried out in the Intensive Care Unit Service of Hospital III EsSalud Chimbote, with the aim of knowing the relationship between nursing care and adverse events presented in the Intensive Care Unit, the sample consisted of 36 patients and 8 nurses, taking into account the inclusion criteria. For data collection, two instruments were applied: "Nursing care observation guide" and "Adverse event registry guide". The data obtained were tabulated, processed and presented in single and double entry tables with numerical and percentage frequencies. Concluding that 22.2% presented adverse events and 38.9% receive a lower quality care. Observing that there is a significant relationship between both variables (p = 0.0495).